Neonatal Arrhythmia - Joshi, A.; Humagain, S. (Kathmandu University Medical Journal, 2020)
Arrhythmias are seldom observed in the newborn period and rarely lead to serious consequences. Because they may be a continuation of fetal arrhythmias, newborn arrhythmias are different from those occurring at later ages. Here we describe a case of a newborn presented with tachycardia at birth. A female baby of 1950 grams born by emergency cesarean section for fetal distress at 36 weeks of gestation. Fetal tachycardia of 251 bpm was detected prenatally. Electrocardiography showed supraventricular tachycardia (SVT). Hematological and biochemical tests done were within normal limits. Echocardiography revealed normal anatomy with severe tachycardia, dilated chambers with moderate to severe TR with moderately reduced ventricle function. For persisting SVT intravenous adenosine was administered with no significant decrease in heart rate, then continuous intravenous amiodarone infusion was started resulting in a transient decrease in heart rate, however again increased, hence baby was started on intravenous digoxin which responded well. Repeated echocardiography showed normal cardiac chambers and function. Baby was discharged on maintenance oral digoxin and was gradually weaned and stopped after 12 months of age. Neonatal arrhythmias is not an uncommon condition in newborns, however it should be early recognized and evaluated for a better outcome of the baby. Although the frequency of arrhythmias in the newborn period is not high, SVT are the most frequently observed arrhythmias in this period.